Real-Time Drowsiness Detection System using Artificial Intelligence - Mohd Fauzi, Muhammad Adib bin Mohd Fauzi; Xavier Ngu, (Evolution in Electrical and Electronic Engineering, 2022)
Many factors have led to car accidents, and one of the main causes is drowsiness. Drinking coffee and getting enough rest are examples of precautions to avoid drowsiness. This study proposes a drowsiness detection technique using artificial intelligence. In this project, a webcam is used to record a video that focuses on the face of the driver. The Viola-Jones algorithm is applied for the face detection process to locate the eyes of the driver in the face region. After doing some training analysis, the system will decide whether the eye of the driver is in a normal or drowsy condition. At the end of this project, a real-time drowsiness detection system using artificial intelligence is introduced. This proposed project needs to be conducted by using a high-spec device to run smoothly in the future.